Evolution of functional recovery using hop test assessment after ACL reconstruction - Rambaud, A. J. M.; Rossi, J.; Neri, T.; Samozino, P.; Edouard, P. (International Journal of Sports Medicine, 2020)
The purpose of this study was to evaluate improvements in functional performance through the use of the Limb Symmetry Index of Single and Triple Hop tests between 12 and 52 weeks after anterior cruciate ligament reconstruction, and to compare these values with usual time-based and performance-based criteria used during the return to sport continuum. Repeated functional assessments using Single and Triple Hop Tests at 12, 16, 22, 26, 39 and 52 postoperative weeks were evaluated. At each session, the median and interquartile range of Limb Symmetry Index of tests were calculated and compared with the usual criteria: return to participation: = 85%, between 12-16 w; return to play: = 90%, between 26-39 w. The results indicate that the median increased over time to 39 postoperative weeks and then stabilized. For Single Hop Test, wide variability was seen at 12 and 16 weeks (interquartile range = 20%); this was lower from 22 to 52 weeks (interquartile range = 8-6%). At 12 weeks for Single Hop Test, the median was 83.6% and did not meet > 85% criteria for return to participation. Hop tests could be interesting functional tests to follow the functional recovery and help decision-making regarding return to participation and return to play.